Effects of Soccer Training on Anthropometry, Body Composition, and Physical Fitness during a Soccer Season in Female Elite Young Athletes: A Prospective Cohort Study - Lesinski, Melanie; Prieske, Olaf; Helm, Norman; Granacher, Urs (Frontiers in Physiology, 2017)
The objectives of this study were to i) describe soccer training (e.g., volume, types), anthropometry, body composition, and physical fitness and ii) compute associations between soccer training data and relative changes of anthropometry, body composition, and physical fitness during a soccer season in female elite young athletes. Seasonal training (i.e., day-to-day training volume/types) as well as variations in anthropometry (e.g., body height/mass), body composition (e.g., lean body/fat mass), and physical fitness (e.g., muscle strength/power, speed, balance) were collected from 17 female elite young soccer players (15.3±0.5 years) over the training periods (i.e., preparation, competition, transition) of a soccer season that resulted in the German championship title in under-17 female soccer. Training volume/types, anthropometrics, body composition, and physical fitness significantly varied over a soccer season. During the two preparation periods, higher volumes in resistance and endurance training were performed (2.00≤d≤18.15; p<0.05), while higher sprint and tactical training volumes were applied during the two competition periods (2.22≤d≤11.18; p<0.05). Body height and lean body mass increased over the season (2.50≤d≤3.39; p<0.01). In terms of physical fitness, significant performance improvements were found over the soccer season in measures of balance, endurance, and sport-specific performance (p<0.05; 2.52≤d≤3.95). In contrast, no statistically significant changes were observed for measures of muscle power/endurance, speed, and change-of-direction speed. Of note, variables of muscle strength (i.e., leg extensors) significantly decreased (p<0.01; d=2.39) over the entire season. Our period-specific sub-analyses revealed significant performance improvements during the first round of the season for measures of muscle power/endurance, and balance (p<0.05; 0.89≤d≤4.01). Moreover, change-of-direction speed significantly declined after the first round of the season, i.e. transition period (p<0.01; d=2.83). Additionally, significant medium-to-large associations were observed between training and anthropometrics/body composition/physical fitness (-0.541≤r≤0.505). Soccer training and/or growth/maturation contributed to significant variations in anthropometry, body composition, and physical fitness outcomes throughout the different training periods over the course of a soccer season in female elite young soccer players. However, changes in components of fitness were inconsistent (e.g., power, speed, strength). Thus, training volume and/or types should be carefully considered in order to develop power-, speed- or strength-related fitness measures more efficiently throughout the soccer season.